Optimization of chemical processes - Edgar, T.F. (Thomas F.); Himmelblau, D.M. (David Mautner). (New York : McGraw-Hill, 1988)
Problem formulation; Optimization theory and methods; Applications of optimization.
Keywords: Chemical processes; Chemical processes; Mathematical optimization